Quality of Urban Parks as Public Spaces Based on Users’ Perceptions (Case Study of Majene City Park) - Zul Asriana; Adam Adam; Serli Serli; Indra Jadil (International Journal Labs, 2025)
Urban parks are one of the important public spaces that function as facilities for social interaction, recreation, and support for urban environmental quality. The quality of urban parks needs to be evaluated periodically to ensure that they meet users’ needs and comfort. This study aims to analyze the quality of Majene City Park as a public space based on users’ perceptions. The research employed a quantitative approach with an explanatory research design. Primary data were collected through questionnaires distributed to 105 park users and supported by field observations, while secondary data were obtained through a literature review. Data analysis was conducted using descriptive statistics with univariate analysis techniques to determine park quality categories based on the variables of user services, activity level, meaningfulness, and accessibility. The results indicate that the overall quality of Majene City Park based on users’ perceptions falls into the fair category, with an average score of 49.78%. Several aspects were rated as good, including seating comfort, vegetation condition, air circulation quality, and accessibility to the park. However, several elements received low ratings, particularly park lighting quality, cleanliness of public toilets, availability of trash bins, diversity of facilities, and clarity of directional signage. These findings suggest that although Majene City Park functions as a public space, improvements in facility quality, cleanliness, safety, and area management are still necessary. In conclusion, optimizing the quality of Majene City Park requires comprehensive improvements through physical arrangement, enhancement of supporting facilities, strengthening of security, and community involvement to ensure that the park functions optimally as a comfortable, safe, and sustainable public space.